Engineering systems analysis of mobility in Odawara city: New transportation services impacts on community engagement - Kimura, Keiji; Moser, Bryan R. (Systems engineering, 2024)
Local cities in Japan are struggling with aging and decreasing populations. Elderly people and parents with young children are uniquely challenged when accessing public transportation, a key to increasing their community engagement and improving local cities' sustainability. This research investigates the introduction of new transportation modes and fares on community engagement of both elderly people and parents of young children. An urban systems model which integrates mobility and civic functions is evaluated by agent‐based simulation to analyze various policies’ impacts on community engagement and financial performance. The model is applied to Odawara City, a typical local city of nearly 200,000 people in Japan. For this case study, two policies which strongly subsidize a community bus and partially subsidize a door‐to‐door van were predicted to generate 10% or greater engagement for the elderly without a financial loss compared to the current baseline case. More specifically, community engagement of elderly people and parents with young children are predicted to increase by 11% with positive (0.25 M yen) net present value per person when the fare of community buses is 100 yen and that of door‐to‐door vans is 300 yen. However, no synergistic effect driven by policies favoring elderly people and those favoring parents is found. Still, the measures to support elderly people's transportation accessibility do not harm the parents’ behavior but rather support their daily activities. The method is demonstrated to be useful for designing new mobility policy in light of a specific population with demographic residential distribution and existing transportation network.